Fostering Adaptive Performance in Employees: A Study on the Impact of Well-being Focused HRM and Leadership Engagement - Ayaz Qaiser; Atif Sheikh; Asif Niaz; Muhammad Noman Nagra (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
This study well-being oriented human resource management practices and engaging leadership joint together covers the gap in understanding the concept of adoptive performance of employee working in banking sector of Pakistan. In addition in depth knowledge as how HRM is implemented by leaders are required based on social exchange theory. There has been broad debate on how HRM improve performance by means of employee well-being measured by happiness at work, trust, exhaustion. The study plan to explore the direct and indirect influence of WBHRM on Adoptive Performance among employees. The data were collected by self-administered questionnaire through convenience sampling technique. Smart PLS and Structural equation modeling (SEM) was utilized for hypotheses testing. Results of the study reveals that well-being oriented human resource management practices that are employee centered are expected to increase well-being and performance.